Implementation of Contextual Teaching and Learning Model ( CTL) to Improve Students' Learning Motivation in Grade 3 SDN Wanoja 01 - Rodiah Rodiah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This research aims to find out the increased motivation of students in grade III SDN Wanoja 1 through ctl model in theme 3, knowing the increase in learning activities of grade III students at SDN Wanoja 1 through ctl model. This research was conducted in grade 3 of Wanoja State Elementary School 01. Data collection in this study uses test-shaped data collection techniques and with non-tests.. From all the data obtained in learning improvement activities through this class action research with the application of contextual teaching and learning approach, can be concluded as follows, the implementation of contextual approach can increase the motivation of Learning in grade 3 sdn Wanoja. This is characterized by the increasing quality of students' spirit and response in solving problems given by teachers, the increasing ability of communication and student work as well as the learning results obtained by students. These improvements include: (a) increasing student cooperation and helping students to solve problems in the learning process (b) increasing inter-student co-operation (c) increasing student involvement in the learning process, contextual learning, has given a new nuance in learning in theme 3 so that learning is more effective.